SOS

25/12/2014 - 23:44 von humbled survivor | Report spam
xy=sinx

x = f(y)=?

http://www.stonetabernacle.com/angl...chord.html

xy=cosx - 1

x = f(y) = ?
 

Lesen sie die antworten

#1 humbled survivor
26/12/2014 - 01:19 | Warnen spam
Carolyn:
Christiansburg, VA Saint Peters, MO


sin(-pi/2) = cos(-pi/2) - 1

(1/t1)*sin(t1)=(cos(t2)-1)/t2

(t2/t1)*sin(t1)=cos(t2)-1

(-3pi/(3pi/2))*sin(3pi/2)=-(cos(-3pi)-1)
-2*sin(3pi/2)=-(cos(-3pi)-1)
2=2

-2*sin(n*pi/2)=-(cos(-n*pi)-1)


"humbled survivor" wrote in message
news:qr0nw.1026097$
xy=sinx

x = f(y)=?

http://www.stonetabernacle.com/angl...chord.html

xy=cosx - 1

x = f(y) = ?


Ähnliche fragen